Environmental determinants and origins of malnutrition - Mata Jiménez, Leonardo (1977)
The characterization of protein-calorie malnutrition (PCM) more than 30 years ago led to its recognition as a scourge of underdeveloped societies (1). For more than two decades, however, PCM was considered a medical problem and was usually dealt with remedially, with little emphasis on correcting the socioeconomic factors that cause it. This was in part due to the emphasis placed on the study of the clinical and biochemical parameters of hospitalized malnourished children (2). There was little understanding of the magnitude of the mild and moderate forms of the disease and their social and economic implications. Recently, a clearer concept of the significance of the mild and moderate forms of PCM has been obtained through interpretation of data on height, weight, food consumption, occurrence of infectious disease, and childhood mortality (3-5). Information on mild and moderate PCM has resulted from long-term prospective studies of rural populations in Africa and Latin America (6-8). It has become evident that malnutrition is an ecological problem requiring a multidisciplinary approach for its study, control and prevention. Research and intervention must be aimed at the environmental components that lead to malnutrition.